FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN NIAT KUNJUNGAN IBU NIFAS KE PELAYANAN KESEHATAN DI WILAYAH KERJA PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Tri Pinaringsih; Emmy Riyanti; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Maternal mortality rate in Semarang of 2015 amounted 112 per 100.000 live births. Most maternal deaths occur in the postpartum (74.29%). Postpartum death can be prevented by post natal care (PNC). Post natal care was done at least 3 times. The aim of this research was to analyze factors related maternal intention to utilize post natal care in the region of Tlogosari Kulon health center, Semarang. This research was a quantitative with cross sectional approach. The study population was all postpartum in April-May. Sampling techinque was using total sampling of 64 people. Data was analyzed using Chi Square statistical analysis test (significance level = 0,05).  The data was collected by interview using questionnaires. The result showed that, a small percentage of respondent in the category of risk in the age range <20 years or >35 years (23.4%), less than half of the respondents were in low education level (29.7%), more than half of the total respondent’s job were housewives (59.4%), a small percentage of respondents who had children were in risk category ≥ 4 children (7.8%), a small percentage of respondents had a pregnancy interval in the risk category <24 months (4.7%), less than half of the respondents were lack of knowledge (46.9%) and more than half of the respondents were utilized postnatal care (67,2%). The conclusion of this research was 65,6% respondents were intend to utilize postnatal care. Based on bivariate test, variables of education (P= 0,046), pregnancy interval (P=0,032), attitude (P=0,002), and perception of behavioral control were related with maternal intention to utilize postnatal care.